Ameliorative effect of taxifolin on gentamicin-induced ototoxicity via down-regulation of apoptotic pathways in mouse cochlear UB/OC-2 cells. Issue 5 (2nd May 2022) - Lin, Jia-Ni; Wang, Jen-Shu; Lin, Chung-Ching; Lin, Hui-Yi; Yu, Szu-Hui; Wen, Yu-Hsuan; Tseng, Guo-Fang; Hsu, Chuan-Jen; Wu, Hung-Pin
Abstract : Background: Taxifolin is a flavanonol with efficacious cytoprotective properties, such as anti-inflammatory, antioxidant, anticancer, hepatoprotective, and nephroprotective effects. However, the potential protective effects of taxifolin against gentamicin-induced ototoxicity have not been confirmed. In this study, the possible mechanisms underlying the effects of taxifolin on gentamicin-induced death of UB/OC-2 cochlear cells were investigated. Methods: Mouse cochlear UB/OC-2 cells with or without taxifolin pretreatment were exposed to gentamicin, and the effects on cytotoxicity, reactive oxygen species (ROS) production, mitochondrial permeability transition, and apoptotic marker expression were examined using biochemical techniques, flow cytometry, western blotting, and fluorescent staining. Results: Little or no apparent effect of taxifolin on cell viability was observed at concentrations less than 40 μM. Further investigations showed that gentamicin significantly inhibited cell viability in a concentration-dependent manner. Pretreatment with taxifolin attenuated gentamicin-induced lactate dehydrogenase release, as well as cellular cytotoxicity. In addition, taxifolin significantly prevented gentamicin-induced cell damage by decreasing ROS production, stabilizing mitochondrial membrane potential, and downregulating the mitochondrial pathway of apoptosis. Conclusion: In summary, pretreatment with taxifolin is effective for mitigating gentamicin-induced apoptotic cell death mediated by the mitochondrial pathway. Our data suggest that taxifolin provides a new approach to combat gentamicin-induced ototoxicity.